2013
DOI: 10.5551/jat.12633
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-and High-Dose Atorvastatin on Carotid Artery Distensibility Using Carotid Magnetic Resonance Imaging ^|^mdash;A Post-Hoc Sub Group Analysis of ATHEROMA (Atorvastatin Therapy: Effects on Reduction of Macrophage Activity) Study

Abstract: Aim:To assess the effect of low-(10 mg) or high-(80 mg) dose atorvastatin on carotid artery distensibility in patients with asymptomatic carotid artery disease using carotid magnetic resonance imaging. Methods: Eighteen patients underwent initial 2-dimensional ECG gated-phase contrast carotid MR imaging and off-line applanation tonometry for distensibility assessment before randomisation to receive low-or high-dose statins and this was repeated at 12 weeks. Phase and magnitude images from the 2-D phase contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
0
10
1
Order By: Relevance
“…It was previously reported that high dose atorvastatin tends to reduce vessel stiffness [34, 35]. In our study, no correlation was found between distensibility and clinical variables.…”
Section: Discussioncontrasting
confidence: 61%
“…It was previously reported that high dose atorvastatin tends to reduce vessel stiffness [34, 35]. In our study, no correlation was found between distensibility and clinical variables.…”
Section: Discussioncontrasting
confidence: 61%
“…31,32 We have also recently demonstrated the contribution of the tumor microenvironment to nerve invasion by cancer. 17,33 This paracrine loop between nerve and tumor cells probably enhances tumor's invasiveness, resulting in patient's dismal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, AS is an independent predictor of survival in the general population [34]. Given that some statins play a role in improvement of renal function and in arterial "destiffening" [27][28][29][30][31]35,36], it has been suggested that the statin dose and the specific compound play a major role in achieving improvement of GFR and reduction of AS and CVD risk [37]. Indeed, statins have been shown to substantially reduce AS in patients with CKD [38].…”
Section: As In Mets-associated Ckdmentioning
confidence: 99%